Laparoscopic transabdominal preperitoneal inguinal repair versus open Lichtenstein repair: a randomized control trial - Manjunath, Darshan A.; Gurugunti, Umeshchandra D.; Radhakrishna, Veerabhadra (International Surgery Journal, 2017)
Background: There have been a plenty of evolution in surgical techniques of hernia repair. The current standard technique is tension-free repair. The different studies show different results with the use of laparoscopy in performing tension-free hernia repair. Hence a study was conducted to compare the laparoscopic transabdominal preperitoneal repair with open Lichtenstein repair regarding operative complications, pain, analgesic usage, and time to return to normal activities. Methods: A randomized control trial was conducted in the Department of General Surgery in a tertiary center from December 2010 to May 2012. All patients underwent either open Lichtenstein repair or laparoscopic transabdominal preperitoneal repair (TAPP). Both the procedures included a recording of operative time, operative complications, pain, analgesic usage, hospital stay, surgical site infection (SSI), and time to return to normal activities. Mann Whitney U test, student ‘t’ test and Fisher’s exact test were used to study the significance of the difference. A p-value <0.05 was considered significant. Results: The open Lichtenstein procedure was found to have a significantly less operative time compared to TAPP procedure (54±15 minutes vs. 75.7±31.6 minutes; p=0.001; CI=95%; Mann Whitney ‘U’ test). TAPP group had a significantly low pain at 12hrs and 24hrs postoperatively. There was no difference between the TAPP group and Lichtenstein group regarding the mean hospital stay (37.2±12.1 hours vs. 38.2±13.6 hours; p=0.7; CI=95%; Mann Whitney ‘U’ test). The mean time to return to work was 12.1±11.8 days in TAPP group, which was significantly lesser than the Lichtenstein group (20.9±4 days; p= 0.04; CI=95%; student ‘t’ test). No recurrence was found. Conclusions: Laparoscopic TAPP was a safe and effective procedure for inguinal hernia repair, and it can replace open procedure.